Geometry of the Solutions of Localized Induction Equation in the Pseudo-Galilean Space - Aydin, Muhittin Evren; Mihai, Adela; Ogrenmis, Alper Osman; Ergut, Mahmut (Hindawi Ltd, 2015)
We study the surfaces corresponding to solutions of the localized induction equation in the pseudo-Galilean space G(3)(1). We classify such surfaces with null curvature and characterize some special curves on these surfaces in G(3)(1).
Keywords: Surfaces